A design navigator to guide the transition towards environmentally benign product/service systems based on LCA results. (20th December 2020) - Neramballi, Abhijna; Sakao, Tomohiko; Willskytt, Siri; Tillman, Anne-Marie
Abstract: With rising societal demands for a transition towards a circular economy and intensifying market competition, manufacturing companies are increasingly seeking alternative ways to design and develop their industrial offerings with reduced environmental impacts and increased value. A possible solution lies in designing environmentally benign product/service systems (PSSs), which often requires the redesign of existing offerings in industrial practice. This article presents a design navigator named lifecycle-oriented function deployment (LFD), which builds on the widely utilized life cycle assessment (LCA) and quality function deployment (QFD) to support the redesign of existing industrial offerings towards PSSs with reduced environmental impacts. LFD includes a novel procedure to derive environmental requirements using LCA and to prioritize them along with customer requirements. It introduces a list of generic service design characteristics to support service design. It also contains a QFD-based procedure to identify design parameters (characteristics and components for both products and services) that have a relatively strong influence on the prioritized requirements. Further, a novel way is proposed to capture specific product and service design characteristics that are feasible to integrate and potentially have a rather strong influence on the requirements when combined. LFD is subsequently applied in a case study to conceptually redesign an existing offering in a manufacturing company. The application is then assessed using an LCA and a semi-structured interview with the users of LFD. The LCA results indicate significant reductions in environmental impacts of the redesigned concepts, and the interview revealed benefits for the practitioners who used LFD. Highlights: Novel LCA based approach to derive environmental design requirements. Novel list of generic service design characteristics to support service design. Filter high impact product-service design parameters from a lifecycle perspective. Integrate product-service design characteristics from a lifecycle perspective. Validated the design navigator together with a manufacturer.